Selective Loss of Signaling Lymphocytic Activation Molecule Family Member 4–Positive CD8+ T Cells Contributes to the Decreased Cytotoxic Cell Activity in Systemic Lupus Erythematosus. Issue 1 (January 2016) - Kis‐Toth, Katalin; Comte, Denis; Karampetsou, Maria P.; Kyttaris, Vasileios C.; Kannan, Lakshmi; Terhorst, Cox; Tsokos, George C.
Abstract : Objective: Engagement of signaling lymphocytic activation molecule family member 4 (SLAMF4; CD244, 2B4) by its ligand SLAMF2 (CD48) modulates the function and expansion of both natural killer cells and a subset of cytotoxic CD8+ T cells. Because the cytotoxicity of CD8+ T lymphocytes isolated from patients with systemic lupus erythematosus (SLE) is known to be impaired, the aim of this study was to assess whether the expression and function of the checkpoint regulator SLAMF4 are altered on CD8+ T cells from patients with SLE. Methods: The expression of SLAMF4 by T cells from healthy donors and patients with SLE was determined by quantitative polymerase chain reaction and flow cytometry. T cells were activated with anti‐CD3 antibody, and degranulation activity was monitored by the surface expression of lysosome‐associated membrane protein 1 (LAMP‐1; CD107a). The SLAMF4+ and SLAMF4− CD8+ T cell subpopulations were characterized by LAMP‐1, perforin, and granzyme B expression and viral peptide–induced proliferation. Results: SLAMF4 gene and surface protein expression was down‐regulated in CD8+ T cells from SLE patients compared with that in cells obtained from healthy donors. Importantly, SLE patients had significantly fewer SLAMF4+ CD8+ T cells compared with healthy donors. SLAMF4− CD8+ T cells from SLE patients had a decreased cytotoxic capacity and decreased proliferative responses to viral peptides. The loss of memory SLAMF4+ CD8+ T cells in SLE patients was linked to the fact that these cells have an increased propensity to lose CD8 expression and become double‐negative T cells. Conclusion: A selective loss of SLAMF4+ CD8+ T cells contributes to the compromised ability of T cells from patients with SLE to fight infection.